Problem Based Learning Terintegrasi Pendekatan Teaching at the Right Level untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Resti Eka Mulyani; Titin Masfingatin; Alip Suparwati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
One of the abilities that students must master in the 21st century is the ability to think critically. This is because the current learning process is not enough with just the ability to remember, but students are also required to have the ability to understand, analyze, and integrate various sources of knowledge to solve problems. Indicators of critical thinking skills are interpretation, analysis, evaluation, and inference. The purpose of this study is to determine the improvement of critical thinking skills and student learning outcomes through the application of the Integrated Problem Based Learning model of the Teaching At The Right Level approach. The research method used is classroom action research which is carried out in two learning cycles. The subjects in this study are students of grade 7C SMPN 13 Madiun. Data on students' critical thinking skills and learning outcomes as supporting data were obtained from the analysis of student worksheets. The results of the study show that the Problem Based Learning learning model integrated with the Teaching At The Right Level learning approach is successful in improving students' critical thinking skills and learning outcomes. The improvement of students' critical thinking skills can be seen from the percentage of critical thinking skills in the pre-cycle of 59.64%, increasing by 3.12% to 62.76% in cycle 1. Then it increased again by 8.66% to 80.73% in cycle 2. The student learning outcomes also experienced a significant increase, namely in the pre-cycle the percentage of student completion was 28.13% with a class average of 53.28. Then in cycle 1 there was an increase of 34.37% to 62.50%, as well as the average class also increased to 73.50. In cycle 2, there was an increase of 15.63% to 78.13%, as well as the average class also increased to 79.34.